A STUDY ON IMPULSIVE BUYING BEHAVIOUR AMONG CONSUMERS IN SHOPPING MALLS (International Journal of Food and Nutritional Sciences, 2022)
Theories of consumer behavior and related research have produced a new concept that can influence the cognitive functions of consumers when purchasing a product. A new trend inconsumer behavior is called "Impulsive Buying". The process of researching consumer behavior has created new opportunities to study unplanned purchases. Unplanned andemotional purchases have a significant impact on a consumer's perceived financial health.The affordability of impulse buying is an obstacle to the regular purchase of planned products. This not only encourages the purchase of a new product but also affects the existingconsumption cycle.